Precise estimation of genomic regions controlling lodging resistance using a set of reciprocal chromosome segment substitution lines in rice - Ookawa, Taiichiro; Aoba, Ryo; Yamamoto, Toshio; Ueda, Tadamasa; Takai, Toshiyuki; Fukuoka, Shuichi; Ando, Tsuyu; Adachi, Shunsuke; Matsuoka, Makoto; Ebitani, Takeshi; Kato, Yoichiro; Mulsanti, Indria Wahyu; et al. (Springer, 2016)
Severe lodging has occurred in many improved rice varieties after the recent strong typhoons in East and Southeast Asian countries. The indica variety Takanari possesses strong culm characteristics due to its large section modulus, which indicates culm thickness, whereas the japonica variety Koshihikari is subject to substantial bending stress due to its thick cortical fibre tissue. To detect quantitative trait loci (QTLs) for lodging resistance and to eliminate the effects of genetic background, we used reciprocal chromosome segment substitution lines (CSSLs) derived from a cross between Koshihikari and Takanari. The oppositional effects of QTLs for section modulus were confirmed in both genetic backgrounds on chromosomes 1, 5 and 6, suggesting that these QTLs are not affected by the genetic background and are controlled independently by a single factor. The candidate region of a QTL for section modulus included SD1. The section modulus of NIL-sd1 was lower than that of Koshihikari, whereas the section modulus of NIL-SD1 was higher than that of Takanari. This result indicated that those regions regulate the culm thickness. The reciprocal effects of the QTLs for cortical fibre tissue thickness were confirmed in both genetic backgrounds on chromosome 9 using CSSLs.